Analisis Pertanyaan Pemahaman Membaca dalam Buku Teks Bahasa Inggris Berdasarkan Taksonomi Bloom yang Direvisi - Laila, Izzatul; Fitriyah, Ima (JET (Journal of English Teaching), 2022)
Reading implies something complex which needs the students to experience, foresee, examine, and admit information based on their background of knowledge. It will be more complex if they lack of Higher Order Thinking Skill (HOTS). HOTS improves reading comprehension and in consequence, the teachers must create a teaching and learning activities that encourage the implementation of HOTS by giving the students high questions found in a suitable textbook. This research was done in order to know the number of reading comprehension questions’ level between HOTS and LOTS. This research conducted using qualitative research approach and content analysis research design because this research focused on analyzing a textbook entitled “Bahasa Inggris” SMA/MA/SMK/MK for 12th grade students published by Ministry of Education and Culture in 2018. The result of this research found 142 reading comprehension questions in total and 83% of them are categorized as LOTS while 17% categorized as HOTS. It indicated that this textbook concentrated more on lower-level than higher-level thinking questions. In conclusion, the teacher must construct their own reading comprehension questions in order to fill the need of the students’ HOTS.